The Effect of Socio-Economic status of Parents, Family Financial Management Education and Learning in Universities Connected with the Financial Literacy of the Students - Irin Widayati (Jurnal Pendidikan Humaniora, 2014)
Pengaruh Status Sosial Ekonomi Orang Tua, Pendidikan Pengelolaan Keuangan Keluarga, dan Pembelajaran di Perguruan Tinggi terhadap Literasi Finansial MahasiswaAbstract: The purpose of this study was to examine the effect of direct and indirect socio-economic status of parents, family financial management education and learning in higher education on financial literacy. Data were collected by through the test and questionnaires. Data analysis techniques with path analysis and regression analysis to test the absolute difference. Results of the study are there is a direct or indirect effect of socio-economic status of parents, family financial management education and learning in higher education towards financial literacy.Key Words: socio-economic status of parents, family financial management education, learning in college, financial literacy Abstrak: Tujuan penelitian ini untuk mengkaji pengaruh langsung maupun tak langsung status sosial ekonomi orang tua, pendidikan pengelolaan keuangan keluarga, dan pembelajaran di perguruan tinggi terhadap literasi finansial. Data dikumpulkan dengan melalui tes dan angket. Teknik analisis data dengan analisis jalur dan analisis regresi dengan uji selisih mutlak. Hasil penelitian adalah terdapat pengaruh langsung maupun tak langsung status sosial ekonomi orang tua, pendidikan pengelolaan keuangan keluarga, dan pembelajaran di perguruan tinggi terhadap literasi finansial. Kata kunci: status sosial ekonomi orang tua, pendidikan pengelolaan keuangan keluarga, pembelajar-an di perguruan tinggi, literasi finansial